Icing characteristics on NGCTR engine inlet for relevant certification conditions - Hoff, S.C. van 't; Ven, H. van der; Norde, E.; Spek, F.; Weide, E. van der (ERF, 2021)
Rotorcraft engine air intakes are known to be particularly sensitive to inflight and ground icing and snow conditions. To allow early identification of geometrical features of the inlet that are sensitive to ice accumulation, the design can benefit from early icing analyses through numerical methods. This paper is focused on the icing assessment and optimisation of the engine intake duct of the Next Generation Civil Tilt Rotor (NGCTR) which is being developed by Leonardo Helicopters. Results for catching efficiency and water catch rates are presented for test cases that have been defined with respect to the operational envelope of the NGCTR and the requirements for atmospheric icing as defined in the EASA certification specifications for large aeroplanes, large rotorcraft and engines. It was found that both the water catch rate and the total water catch are lower for the NGCTR in conversion flight compared to the NGCTR in airplane flight conditions. Additionally, ground operations of the NGCTR are not found to be critical for icing in/on the engine inlet due to supercooled droplets.